Impact of supplemental phosphorus source on phosphorus utilization in lactating dairy cattle - Bradford, Barry J.; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplemental phosphorus (P) in various forms and sources (pellet, meal, liquid, and corn dried distillers grains with solubles; DDGS) were compared in 12 multiparous Holstein cows producing 94.8 lb of milk (115 ± 55 days in milk) in a 4 × 4 Latin square with 21-day periods. The pellet and meal diets contained monocalcium phosphate with a wheat middlings carrier, and the liquid diet contained ammonium polyphosphate in a cane molasses base. The DDGS supplied an organic P source. Cows were blocked by parity, days in milk, and milk production and randomly assigned to treatments. Phosphorus intakes were similar among all 4 diets (116, 116, 119 and 118 g/day for pellet, meal, liquid and DDGS diets, respectively). Cows consuming the liquid diet experienced greater (P < 0.001) sugar intakes. Milk yield differed (P = 0.05) among diets, with the DDGS diet yielding the most milk (76.3, 78.1, 75.2 and 80.5 lb/day for pellet, meal, liquid, and DDGS diets, respectively). There were no differences in milk fat and milk protein percentages or in daily lactose production. Excretion of P in feces tended (P = 0.07) to differ among treatments (67.4, 66.3, 57.5, and 60.0 g/day for pellet, meal, liquid and DDGS diets, respectively), resulting in a trend (P = 0.10) for greater P retention from diets, resulting in less P excretion. Secretion of P in milk did not differ among treatments. These data show that supplemental P source does not affect dry matter intake or P intake. Phosphorus source resulted in slight differences in P utilization, but it was not related to sorting of the diet. The DDGS diet showed responses similar to those of inorganic P mineral supplements and had favorable production yields, indicating that DDGS is an adequate substitute for mineral sources of P.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dairy; Dried distillers grains; Feces; Phosphorus; Milk yield